School Gardens: Initial Training of Future Primary School Teachers and Analysis of Proposals - José Orenes Cárceles; Gabriel Enrique Ayuso Fernández; Manuel Fernández-Díaz; José María Egea Fernández (MDPI AG, 2022)
This paper describes a training proposal for future teachers in the design, management, and use of school gardens as an educational resource. During the 2020/2021 academic year, future teachers in the 4th grade of Primary Education (last year of the University Degree) received theoretical-practical classes to develop teaching-learning activities in the area of Sciences that they implemented in a Primary school. This training proposal and the research activities designed and implemented in the school garden by future teachers were analysed using three criteria: curricular contents covered, competency richness and structure and content. From the training programme implemented, we highlight an increase in the motivation of students towards learning to use this resource; because it is learned "in situ" in the school garden, it is possible to carry out outdoor work, sharing natural resources through cooperative work and improving relationships. Regarding the design of activities proposed by the future teachers, there is a predominance of the use of observation and classification processes and a deficit of other scientific competences, which implies the need for greater specific initial training on school gardens.